Outcome and effect of vaccination in SARS-CoV-2 Omicron infection in hemodialysis patients: a cohort study. Issue 10 (29th June 2022) - Ashby, Damien R; Caplin, Ben; Corbett, Richard W; Asgari, Elham; Kumar, Nicola; Sarnowski, Alexander; Hull, Richard; Makanjuola, David; Cole, Nicholas; Chen, Jian; Nyberg, Sofia; Forbes, Suzanne; et al.
ABSTRACT: Background: Hemodialysis patients are at high risk of Covid-19, though vaccination has significant efficacy in preventing and reducing the severity of infection. Little information is available on disease severity and vaccine efficacy since the dissemination of the Omicron variant. Methods: In a multi-center study, during a period of the epidemic driven by the Omicron variant, all hemodialysis patients positive for SARS-CoV-2 were identified. Outcomes were analyzed according to predictor variables including vaccination status. Risk of infection was analyzed using a Cox proportional hazards model. Results: SARS-CoV-2 infection was identified in 1126 patients including 200 (18%) unvaccinated, 56 (5%) post first dose, 433 (38%) post second dose, and 437 (39%) at least 7 days beyond their third dose. The majority of patients had a mild course but 160 (14%) were hospitalized and 28 (2%) died. In regression models adjusted for age and comorbidity, two-dose vaccination was associated with a 39% (95%CI: 2%–62%) reduction in admissions, but third doses provided additional protection, with a 51% (95%CI: 25%–69%) further reduction in admissions. Among 1265 patients at risk at the start of the observation period, SARS-CoV-2 infection was observed in 211 (17%). Two-dose vaccination was associated with a 41% (95%CI: 3%–64%) reduction in the incidence of infection, with no clear additional effect provided by third doses. Conclusions: These data demonstrate lower incidence of SARS-CoV-2 infection after vaccination in dialysis patients during an Omicron dominant period of the epidemic. Among those developing infection, severe illness was less common with prior vaccination, particularly after third vaccine doses.